THE PLACE OF THE PENCIL DRAWING DIRECTION OF FINE ARTS IN SCHOOLS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article reveals the special place of fine art among the types of art. Starting from general secondary education, paying deep attention to the types, forms and features of fine art, the views of the pencilfine art, illusionism, pencil drawing image, which is considered its foundation, are highlighted.